Macroeconomic Effects of Fiscal Policies: Empirical Evidence from Bangladesh, People's Republic of China, Indonesia, and Philippines - Geoffrey Ducanes; Marie Anne Cagas; Duo Qin; Pilipinas Quising; Mohammad Abdur Razzaque (Asian Development Bank (ADB), 2006)
Fiscal expansion in Bangladesh, the People's Republic of China, Indonesia, and the Philippines via increased spending is typically more effective than fiscal expansion via tax rate reduction for stimulating growth. On the other hand, the effectiveness of expenditure versus tax-side automatic stabilizers differs across countries. This paper studies the macroeconomic effects of fiscal policies in four Asian countries - Bangladesh, the People's Republic of China, Indonesia, and the Philippines - by means of structural macroeconometric model simulations. It is found that short-term fiscal multipliers from an untargeted increase in government expenditure are positive but much less than those from an increased expenditure targeted to capital spending. The multiplier effects from fiscal expansion via a tax rate reduction are found to be typically much less than through higher spending. The effectiveness of automatic stabilizers in general, and more specifically, the effectiveness of expenditure versus tax-side stabilizers, differs across countries.
hdl:11540/2568
Keywords: 330